Wastewater Irrigation: A Study of Power Relations and Community Dynamics - Khalid, Maria; Khan, Izhar Ahmad; Farah, Naveed; Rasul, Fahd (Biological and Clinical Sciences Research Journal, 2025)
Wastewater irrigation has emerged as a critical practice in addressing canal water scarcity and enhancing agricultural productivity. Objectives: This study explores the socio-political implications of using untreated wastewater for irrigation, emphasizing the complex interplay between water management, governance, and social equity. Methodology: By analyzing case studies from various wastewater-using communities, the paper highlights how wastewater irrigation in vegetable production can alleviate and exacerbate existing socio-political tensions, particularly regarding access to water resources, public health concerns, and food sustainability. Results: The study examines stakeholders' perceptions and the farming community’s responses to wastewater irrigation. It’s shedding light on the governance challenges in managing this multifaceted issue. Ultimately, this paper argues the drawbacks of using wastewater and the need for effective irrigation practices that require technological innovations, inclusive political discourse, and community involvement to address the underlying power dynamics. Conclusion: The findings highlight the necessity for interdisciplinary approaches to manage wastewater and irrigation sustainably and equitably in the face of increasing wastewater and water demands for irrigation